2020
DOI: 10.5455/pbs.20200615090037
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Impulsivity and Aggression As Substrates of Suicidal Behavior: A Narrative Focus on the Involvement of Serum Lipids

Abstract: Previous incidental findings of an increase of suicidal risk among subjects with low cholesterol levels have drawn attention to the role of lipids in suicidal behavior. To date, multiple lines of evidence acquired from clinical studies have confirmed an association between low cholesterol levels and suicidal behavior, but the involvement of dimensional traits including impulsivity and aggression in this association remains elusive. In this narrative review, we aimed to address and synthesize the literature reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 102 publications
(139 reference statements)
0
0
0
Order By: Relevance
“…Similarly, a literature review conducted by Troisi A. it reflects contradictory data, and therefore, it becomes obvious to the author that there are certain subgroups of vulnerable people who, unlike most people in the general population, are subject to adverse psychological and behavioural consequences associated with a low level of CH [76]. The authors of another literature review, who have covered the literature for 40 years, found more evidence of the existence of a connection, but still could not miss the contradictions [77]. There is conflicting information about the role of statins in suicidal behaviour.…”
Section: Neutral Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a literature review conducted by Troisi A. it reflects contradictory data, and therefore, it becomes obvious to the author that there are certain subgroups of vulnerable people who, unlike most people in the general population, are subject to adverse psychological and behavioural consequences associated with a low level of CH [76]. The authors of another literature review, who have covered the literature for 40 years, found more evidence of the existence of a connection, but still could not miss the contradictions [77]. There is conflicting information about the role of statins in suicidal behaviour.…”
Section: Neutral Positionmentioning
confidence: 99%
“…There is conflicting information about the role of statins in suicidal behaviour. Several authors note that in patients treated with statins, the frequency of suicidal thoughts increased, but no connection was found with dietary habits, diets [77,78]. In a meta-analysis that studied methods of reducing cholesterol and the relationship with suicide, it was noted that statins do not affect suicide in any way, unlike nutrition [79].…”
Section: Neutral Positionmentioning
confidence: 99%